The Impacts of Black Soldier Fly Frass on Nitrogen Availability, Microbial Activities, C Sequestration, and Plant Growth - Gebremikael, Mesfin T.; Wickeren, Niklas van; Hosseini, Pezhman S.; De Neve, Stefaan (Frontiers in Sustainable Food Systems, 2022)
Using insects, notably black soldier fly (BSF), is becoming one of the emerging technologies to valorize agrifood waste into high-value products, such as proteins for animal feed. Its market is expected to grow more rapidly following the new European legislation extending larvae protein use in poultry farming. The anticipated increase in larvae protein also results in a parallel increase in frass, a residue leftover after rearing the larvae and selling as a biofertilizer. Little is known about the impacts of frass made from different feedstocks used for raising the larvae on plant growth and soil quality. We set up an incubation and pot experiment to understand their effect on plant growth and soil quality and tested seven frass fertilizers made from various types of food waste and anaerobic digestate and potato pulp as reference materials using maize as a test plant. We found that the effect of frass on N availability and soil microbial quality significantly (p < 0.05) varied depending on the feedstock used for rearing the BSF larvae. N immobilization occurred up to more than 70 days, and 4–20% net N was released at the end of the 103-day-long experiment. In line with N availability dynamics, most of the frass treatments did not significantly increase the plant growth. All frasses significantly increased the microbial biomass C and enzyme activities. About 56–70% of the applied C in frass is estimated to be stable in the soil. Our data confirm that frass is a valuable product to improve soil quality but need to be applied with N sources that are readily available to avoid nutrient shortage during plant growth.